Feminisme dalam karya tari kontemporari dan kehidupan Aida Redza / Azura Abal Abas - Azura, Abal Abas (2017)
This thesis examines Aida Redza’s contemporary dance works and her life between 1995 and 2003. Contemporary dance form in Malaysia is different from the contemporary dance in the West. While contemporary dance is a genre that generally refers to now or present, the contemporary dance genre that exists in Malaysia is a combination of local traditional dance elements and contemporized modern dance elements from the west. As a pioneer Malay female choreographer since the 1990s, Aida actively stages Malay women's domestic plight through her choreographies. Her works grapples with the topic of feminism, particularly on gender inequality, where Malay women, portrayed as wives, are shown to be placed on a subordinated role in relation to men, their husbands. As a woman who grew up in a modern Malay family and had opportunities to study dance abroad, Aida’s dance pieces during the eight years understudy complicates and subverts the notion of women as submissive homemaker. Her works depict real life scenes of domestic conflicts between husband and wife, those that normally would not be openly discussed in the public. Such works are Ta'a (1995), Zik'r (Beyond Words, 1996), Stirring (2002) and Tiga Naga (2003). Aida uses her choreographies to make bold feminist statements from the perspective of a Malay Muslim woman. Aida’s selected works grew as a result of her rising concern for equal rights or power distribution and these works provided a platform for her to reflect, question, and criticize gender inequality as seen practiced in the Malay family and Malay culture.